2016
DOI: 10.4314/ejhs.v26i5.7
|View full text |Cite
|
Sign up to set email alerts
|

An <i>in vitro</i> evaluation of the accuracy of two electronic apex locators to determine working length in the presence of various irrigants

Abstract: BACKGROUND: Cleaning and shaping of root canal system requires various irrigating solutions. The question is whether the presence of irrigation solution alters working length determination using apex locators. The purpose of this study was to compare the accuracy of Root ZX and i-Root apex locator for determining working length in the presence of different irrigating solution. MATERIALS AND METHOD: Eighty extracted single rooted human teeth were used. The teeth were sectioned at Cemento Enamel Junction (CEJ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
(20 reference statements)
1
5
1
3
Order By: Relevance
“…It uses frequencies of 5 KHz and 500 Hz. The manufacturer guarantees that its accuracy is good even in the presence of various canal contents [10]. However, our results differed from those in some of the previous studies in which the irrigants used did not affect the accuracy of different EALs, such as Root ZX, in determining root canal perforations [20].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…It uses frequencies of 5 KHz and 500 Hz. The manufacturer guarantees that its accuracy is good even in the presence of various canal contents [10]. However, our results differed from those in some of the previous studies in which the irrigants used did not affect the accuracy of different EALs, such as Root ZX, in determining root canal perforations [20].…”
Section: Discussioncontrasting
confidence: 66%
“…i-Root (S-Denti Co. Ltd Seoul, Korea) apex locator uses different frequencies (i.e., 5 KHz and 500 Hz). The manufacturer claims that its accuracy is good irrespective of canal contents [10].…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…Erdemir et al showed no significant difference in file tip position between 2.5% NaOCl and 0.2% chlorhexidine gluconate using a Tri Auto ZX [21]. There were no differences in the accuracy of endometric measurements in the presence of sodium hypochlorite and CHX in the Prasad [42] and Gomes [43] studies. Different results were obtained by Özsezer et al in an in vivo study; they evaluated the performance of Propex after extirpation and in the presence of different irrigation solutions, including 2.5% NaOCl and 0.2% chlorhexidine gluconate.…”
Section: Discussionmentioning
confidence: 99%
“…Buna karşın, Prasad ve ark. 32 kök kanalında, aralarında % 2'lik KH'nin de bulunduğu, farklı solüsyonların varlığında Root ZX ve I-Root'un (S-Denti, Seul, Kore) doğruluğunun anlamlı olarak etkilendiğini NaOCl ve CHX gibi daha iletken çözeltilerde büyük sapma meydana geldiğini ve % 2'lik KH'in en büyük sapmayı gösterdiğini, ancak bunun klinik olarak anlamlı olmadığını belirtmişlerdir. EDTA EDTA, kök kanal dentinindeki kalsiyum iyonları ile oluşturduğu şelasyon özelliği sayesinde dentinin inorganik yapısını uzaklaştırması ve bu etkileşimin sonucu olarak da kök kanalının şekillendirilmesini kolaylaştırması özelliğiyle endodontide yaygın kullanılan bir yıkama solüsyonudur.…”
Section: Naoclunclassified